Regionalization and indicators of basic sanitation services in Alto Piranhas: an analysis of the transition to the new legal framework - Formiga, José Alves; Bresciani, Luís Paulo; Machado Júnior, Celso; Barbosa, Erivaldo Moreira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
This research presents the systematization of the regional indicators of Alto Piranhas, by comparing the indices of the municipalities that belong to the Metropolitan Area around the city of Sousa, in the state of Paraíba, Brazil, with a focus on the transition to the new legal framework. Methodologically, this study is a document research. For quantitative indicators of water supply and sewage in the municipalities that belong to the Metropolitan Area of the city of Sousa, searches were conducted in five databases: the National Information System on Sanitation (SNIS, Sistema Nacional de Informações sobre Saneamento, in Portuguese), the Getúlio Vargas Foundation (FGV-DATASAN, Fundação Getúlio Vargas, in Portuguese), the Brazilian Institute of Geography and Statistics (IBGE, Instituto Brasileiro de Geografia e Estatística, in Portuguese), the National Forum of Metropolitan Entities (FNEM, Fórum Nacional de Entidades Metropolitanas, in Portuguese), and the Brazil Sanitation Panel (Painel Saneamento Brasil, in Portuguese) of the Trata Brasil Institute (Instituto Trata Brasil, in Portuguese). The results showed that CAGEPA is the public agency for basic sanitation in the cities of Aparecida, Nazarezinho, Santa Cruz, São Francisco, São José da Lagoa Tapada, Marizópolis, Lastro, and Vieirópolis; it is responsible for planning, executing and operating basic sanitation services, which includes collecting, adducting, treating and distributing water plus collecting, treating and finally disposing of sewage. In the case of DAESA, the study identified organizational and structural issues regarding the availability of data on basic sanitation in the city of Sousa, which hinders an in-depth analysis of that municipality's supply profile. This considered, we concluded that having access to the indicators of basic sanitation services in the Metropolitan Area of Sousa leads to setting more objective goals towards optimizing the sanitation services in the region.